Unsupervised Facial Action Representation Learning by Temporal Prediction - Wang, Chongwen; Wang, Zicheng (Frontiers in Neurorobotics, 2022)
Due to the cumbersome and expensive data collection process, facial action unit (AU) datasets are generally much smaller in scale than those in other computer vision fields, resulting in overfitting AU detection models trained on insufficient AU images. Despite the recent progress in AU detection, deployment of these models has been impeded due to their limited generalization to unseen subjects and facial poses. In this paper, we propose to learn the discriminative facial AU representation in a self-supervised manner. Considering that facial AUs show temporal consistency and evolution in consecutive facial frames, we develop a self-supervised pseudo signal based on temporally predictive coding (TPC) to capture the temporal characteristics. To further learn the per-frame discriminative-ness between the sibling facial frames, we incorporate the frame-wisely temporal contrastive learning into the self-supervised paradigm naturally. The proposed TPC can be trained without AU annotations, which facilitates us using a large number of unlabeled facial videos to learn the AU representations that are robust to undesired nuisances such as facial identities, poses. Contrary to previous AU detection works, our method does not require manually selecting key facial regions or explicitly modeling the AU relations manually. Experimental results show that TPC improves the AU detection precision on several popular AU benchmark datasets compared with other self-supervised AU detection methods.